2009
DOI: 10.1080/15459620902810083
|View full text |Cite
|
Sign up to set email alerts
|

Training Health and Safety Committees to Use Control Banding: Lessons Learned and Opportunities for the United States

Abstract: Control banding (CB) is a control-focused risk management model that has received international attention. CB strategies are designed to control workplace chemical exposures after the completion of a qualitative risk assessment. Connecticut was one of the first states to provide training on how to use this control-focused tool. Joint labor/management teams and individuals from 34 workplaces attended a control banding workshop and learned how to use one CB model, the United Kingdom (UK) Health and Safety Execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Russell et al (1998) reported that the exposure control levels recommended in the COSHH Essentials strategy were frequently in agreement with, or more stringent than, expertly derived health-based OELs. These findings were similar to those reported by Bracker, Morse, and Simcox (2009) in which the application of COSHH Essentials exposure bands were in general agreement (65%) with the exposure evaluations conducted by a certified industrial hygienist. Tischer et al (2003) also found reasonably good agreement between the COSHH Essentials exposure bands and measured airborne concentrations of solids and organic solvents (when used in medium quantities), but found that exposure concentrations could exceed predicted ranges when small quantities of organic solvents (medium/high volatility) were used.…”
Section: Discussionsupporting
confidence: 91%
“…Russell et al (1998) reported that the exposure control levels recommended in the COSHH Essentials strategy were frequently in agreement with, or more stringent than, expertly derived health-based OELs. These findings were similar to those reported by Bracker, Morse, and Simcox (2009) in which the application of COSHH Essentials exposure bands were in general agreement (65%) with the exposure evaluations conducted by a certified industrial hygienist. Tischer et al (2003) also found reasonably good agreement between the COSHH Essentials exposure bands and measured airborne concentrations of solids and organic solvents (when used in medium quantities), but found that exposure concentrations could exceed predicted ranges when small quantities of organic solvents (medium/high volatility) were used.…”
Section: Discussionsupporting
confidence: 91%
“…Bracker et al (2009) performed a survey of participants who had used the COSHH Essentials model in their facility after training and reported difficulty in finding R-phrases. The same issue was also noted from the experiences of the web-based model by the authors in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries would support the use of fully validated CB tools as a screen for the purpose of prioritizing exposure measurements. Such a strategy would be valuable in assisting companies to comply with the Registration, Evaluation, Authorization, and Restriction of Chemicals regulation (REACH) (European Union, 2006; Tielemans et al , 2007; Bracker et al , 2009; Ogden, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…This technique provides guidance specifically for SMEs on controlling the use of chemicals for a range of common industrial tasks (162). Other qualitative CB programs have been developed in the last 10 years including the International Labour Organization Toolkit, Belgium-REGETOX, Norway-KjemiRisk, and Netherlands Stoffenmanager (79,163). The margins of safety afforded by qualitative CB programs have been questioned and the authors stated the following:…”
Section: Control Bandingmentioning
confidence: 99%